Temporary external fixation for low back pain: Is it worth doing? - Faraj, A. A. (Springer-Verlag, 1997)
Thirty-three patients with low back pain underwent spinal fusion following a positively predicting external fixation test. Thirty-two spinal fusions and one sacroiliac joint fusion were performed. The complications following the use of the external fixator were significant. The results following spinal fusion were not related to the positive response to the external fixator. Multiple variables affect the results of spinal fusion. We feel that the external fixator test in low back pain management is very invasive, and its use cannot be justified.